2013
DOI: 10.1155/2013/507910
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Global Cognitive Function Predict E-Mail but Not Internet Use in Heart Failure Patients

Abstract: Background. The internet offers a potential for improving patient knowledge, and e-mail may be used in patient communication with providers. However, barriers to internet and e-mail use, such as low health literacy and cognitive impairment, may prevent patients from using technological resources. Purpose. We investigated whether health literacy, heart failure knowledge, and cognitive function were related to internet and e-mail use in older adults with heart failure (HF). Methods. Older adults (N = 119) with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Several studies from 2013 evaluated the use of the secure messaging feature of a patient portal [15,16,20,22,23]. These studies all demonstrated a high level of patient satisfaction with the feature, and the users did not feel the process to exchange SMs was too complicated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies from 2013 evaluated the use of the secure messaging feature of a patient portal [15,16,20,22,23]. These studies all demonstrated a high level of patient satisfaction with the feature, and the users did not feel the process to exchange SMs was too complicated.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from 2013 also demonstrated several barriers to use of the patient portal; most common were lack of Internet access and lack of technical support [19,20,22,23]. Another significant finding in 2013 was the association of patient portal use with medication adherence, disease control, self-maintenance of health, and including the patient in the medical decision [16,19,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…The S-TOFHLA is a shortened version of the Test of Functional Health Literacy [55], which correlates with the REALM [56]. In another systematic review of health literacy using web-based health information environments [26], the Newest Vital Sign was used most often [57], followed by the REALM [58]. There is a lack of standard measurement tools to evaluate health literacy [17,22,[59][60][61][62].…”
Section: Measurement Of Health Literacymentioning
confidence: 99%
“…One major concern with low literacy can be linked to reduced selfcare behaviors in cardiac patients. In addition, low health literacy has been associated with lower BP control and reduced participation in medical decisions, 101,111 reduced communication with providers, 120 lower disease knowledge, 103,104,115 reduced cognition, 112 lower medication adherence levels, 123 and lower medication refill adherence.…”
Section: Question 3 How Are Common Barriers To Implementing Tpe For mentioning
confidence: 99%
“…HF patients could be inappropriately categorized as having inadequate or marginal health literacy because of the time limit; therefore, health literacy measures that are specifically intended for an older population might be warranted. The METER (Medical Term Recognition Test), 120 the CAHPS (Consumer Assessment for Healthcare Providers and Systems), 107 the NVS (Newest Vital Sign Instrument), 116 and the BHLS (Brief Health Literacy Screen) 111 have also been used, but there is no TPE Interventions for Self-Management specific literature reported on use among cardiac patients. On the basis of the current evidence, clinicians need to consider psychometric properties of health literacy screening tools (eg, reliability, validity, sensitivity) related to cardiac patient population characteristics.…”
mentioning
confidence: 99%